Contamination in TESS Light Curves: The Case of the Fast Yellow Pulsating Supergiants - Pedersen, May G.; Bell, Keaton J. (The Astronomical journal, 2023)
Given its large plate scale of 21″ pixel −1 , analyses of data from the Transiting Exoplanet Survey Satellite (TESS) space telescope must be wary of source confusion from blended light curves, which creates the potential to attribute observed photometric variability to the wrong astrophysical source. We explore the impact of light curve contamination on the detection of fast yellow pulsating supergiant (FYPS) stars as a case study to demonstrate the importance of confirming the source of detected signals in the TESS pixel data. While some of the FYPS signals have already been attributed to contamination from nearby eclipsing binaries, others are suggested to be intrinsic to the supergiant stars. In this work, we carry out a detailed analysis of the TESS pixel data to fit the source locations of the dominant signals reported for 17 FYPS stars with the Python package TESS _ localize . We are able to reproduce the detections of these signals for 14 of these sources, obtaining consistent source locations for four. Three of these originate from contaminants, while the signal reported for BZ Tuc is likely a spurious frequency introduced to the light curve of this 127 day Cepheid by the data processing pipeline. Other signals are not significant enough to be localized with our methods, or have long periods that are difficult to analyze given other TESS systematics. Since no localizable signals hold up as intrinsic pulsation frequencies of the supergiant targets, we argue that unambiguous detection of pulsational variability should be obtained before FYPS are considered a new class of pulsator.